Implikatur Percakapan dalam Film Penyalin Cahaya Karya Wregas Bhanuteja - Afiqah Dien Ramadhani; Aisyah Nur Faizah; Era Nur’aini; Naili Nazilatur Rohmah; Siti Mutmainah; Asep Purwo Yudi Utomo; Amilia Buana Dewi Islamy; Sri Isnani Setiyaningsih (Universitas Palangka Raya, 2026)
This study aims to describe conversational implicatures found in the utterances of characters in the film Penyalin Cahaya directed by Wregas Bhanuteja. This research employs a descriptive qualitative approach with a pragmatic analysis method. The data consist of utterances containing conversational implicatures, collected through observation and note-taking techniques by repeatedly watching the film and recording dialogues relevant to the research focus. The collected data were then analyzed using the distributional method to identify forms of utterances, supported by contextual analysis to interpret the implied meanings within the conversations. The results show that the characters’ utterances in the film contain various forms of conversational implicature used to convey meaning indirectly. These implicatures arise based on situational context, relationships between characters, and events underlying the conversations. Furthermore, implicatures reflect social dynamics in character interactions, such as doubt, rejection, pressure, and self-protection efforts. Therefore, this study demonstrates that the use of conversational implicature in film plays an important role in delivering implicit messages and strengthening the meaning conveyed in dialogue.